2017
DOI: 10.1364/oe.25.014598
|View full text |Cite
|
Sign up to set email alerts
|

Combining freeform optics and curved detectors for wide field imaging: a polynomial approach over squared aperture

Abstract: Abstract:. In the recent years a significant progress was achieved in the field of design and fabrication of optical systems based on freeform optical surfaces. They provide a possibility to build fast, wide-angle and high-resolution systems, which are very compact and free of obscuration. However, the field of freeform surfaces design techniques still remains underexplored. In the present paper we use the mathematical apparatus of orthogonal polynomials defined over a square aperture, which was developed befo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…To facilitate the further explanations we provide sag diagrams for the 4 th to 11 th modes of each set on Figure 1 (the piston, tip and tilt are the same, so they are excluded). It is necessary to mention that a freeform surface can be described by any of these polynomial sets, but due to some features of the numerical optimization process one way of the freeform description can be preferable [20].…”
Section: Freeform Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the further explanations we provide sag diagrams for the 4 th to 11 th modes of each set on Figure 1 (the piston, tip and tilt are the same, so they are excluded). It is necessary to mention that a freeform surface can be described by any of these polynomial sets, but due to some features of the numerical optimization process one way of the freeform description can be preferable [20].…”
Section: Freeform Descriptionmentioning
confidence: 99%
“…Optical design of the POLLUX instrument MUV channel: (a) general view, (b) zoom-in of the polarimetric unit.tended UV region 90-390 nm[20]. Such a high resolution can be achieved in an instrument with 3 channels, when each of them represents an echelle spectrograph.…”
mentioning
confidence: 99%
“…In order to design the ideal survey for this type of observations, one would choose: a place with the lowest skybackground level; a telescope without obscuration, as any obscuration or spider causes diffraction and displace more power in the point spread function (PSF) towards the wings (Singaravelu & Cabanac 2014;Hugot et al 2014;Muslimov et al 2017a); a fast optical system with a small f /D (where f is the focal length and D is the diameter of the entrance pupil), as for extended objects the imaging speed depends on the focal ratio (not on the aperture size, as for point-source objects); it should have either only refractive elements with anti-reflection coatings (e.g. Abraham & van Dokkum 2014), or superpolished reflective surfaces, and no dust contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Rim et al [1] and Stamenov et al [2] demonstrated a potential reduction of lenses, leading to compactness, better resolution and improved illumination with monocentric systems using a curved focal plane. Iwert et al and Muslimov et al [3,4] showed new ways to create telescopes and optical instruments with higher resolution for astronomical applications. Reshidko et al [5] demonstrated the possibility to create miniature lenses for mobile phone applications with faster apertures.…”
Section: Introductionmentioning
confidence: 99%